Strategies of Development Potentialsi Carved Souvenir Crafts in Nagari Pandai Sikek, Tanah Datar District (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The purpose of this study was to determine the potential development strategy for carving souvenir crafts in Pandai Sikek village, X Koto District, Tanah Datar Regency. This study uses descriptive qualitative research methods through field observations, interviews and documentation. The technique used in this study is the SWOT analysis technique. From the results of the research, five Pandai Sikek souvenirs were found. Nine name motifs from seven traditional Minangkabau carvings were found on five souvenir prints. The typical souvenirs of Pandai Sikek are made of Suria wood, the process uses tools in the form of flying chisels and Sodok chisels.